2020
DOI: 10.1210/jendso/bvaa046.623
|View full text |Cite
|
Sign up to set email alerts
|

SAT-049 Testosterone Therapy Reduces Inflammatory Activation of Human Monocytes in Hypogonadal Type-2 Diabetic Men as a Potential Mechanism to Improve Atherosclerosis

Abstract: Testosterone deficiency is prevalent in men with type 2 diabetes (T2D) and is associated with greatly elevated risk of cardiovascular mortality. Testosterone replacement has beneficial effects on surrogate markers and risk factors of atherosclerosis including inflammation, cholesterol and insulin resistance improving survival in men with T2D. The underlying mechanisms of this action remain poorly understood. Inflammation is a central feature to both T2D and atherosclerosis and is driven by monocyte/macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The influence of testosterone and cortisol on monocytes has been previously reported. In diabetic patients with hypogonadism, testosterone therapy reduced inflammatory activation of human monocytes [ 66 ]. It has also been found that cortisol signaling through the mineralocorticoid receptor, under oxidative stress, may promote monocyte inflammatory activation [ 67 ][ 68 ], so a reduction in cortisol would also be favoring the reduction of activated monocytes, especially in the context of rising testosterone levels.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of testosterone and cortisol on monocytes has been previously reported. In diabetic patients with hypogonadism, testosterone therapy reduced inflammatory activation of human monocytes [ 66 ]. It has also been found that cortisol signaling through the mineralocorticoid receptor, under oxidative stress, may promote monocyte inflammatory activation [ 67 ][ 68 ], so a reduction in cortisol would also be favoring the reduction of activated monocytes, especially in the context of rising testosterone levels.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of testosterone and cortisol on monocytes has been previously reported. In patients with diabetes with hypogonadism, testosterone therapy reduced inflammatory activation of monocytes ( 82 ). It has also been indicated that cortisol signaling through the mineralocorticoid receptor, under oxidative stress, may promote monocyte inflammatory activation ( 83 , 84 ); thus, a reduction in cortisol would also be favoring the reduction of activated monocytes, particularly in the context of rising testosterone levels.…”
Section: Discussionmentioning
confidence: 99%